Front Cover: Implications of Guanidine Substitution on Copper Complexes as Entatic‐State Models (Eur. J. Inorg. Chem. 29/2016). Issue 29 (October 2016) - Hoffmann, Alexander; Stanek, Julia; Dicke, Benjamin; Peters, Laurens; Grimm‐Lebsanft, Benjamin; Wetzel, Alina; Jesser, Anton; Bauer, Matthias; Gnida, Manuel; Meyer‐Klaucke, Wolfram; Rübhausen, Michael; Herres‐Pawlis, Sonja
Abstract : The cover picture shows a guanidine–quinoline–copper complex as a new entatic‐state model. Small changes in the ligand strongly affect the molecular structure, which demonstrates the subtle balance of steric and electronic effects at a metal center. The unique combination of solid‐state and solution structural investigations by classical single‐crystal X‐ray diffraction and X‐ray absorption spectroscopy together with density functional theory reveals deep insights into this entatic‐state model. Details are discussed in the article by S. Herres‐Pawlis et al. onp. 4731 ff . For more on the story behind the cover research, see theCover Profile .